The Expressions Of Ngalem In The Javanese Society In Kebumen Regency - Purwaningrum, Prapti Wigati; Harmoko, Danang Dwi; Wibowo, Ary Iswanto; Nisa, Baiatun (Wanastra: Jurnal Bahasa dan Sastra, 2024)
This research is based on the use of "ngalem" or praising oral speech in daily communication. “Ngalem” is an expression to show admiration for other people. Nowadays, the use of this term is rarely use in Javanese society. This research aims to describe and explain the types of metaphors found in Javanese speech when someone "ngalem" or praises another person. Next, provide data using the listen and note method. There are several findings, first, "ngalem" or praise is usually intended to praise the beauty of male and female body parts including the head, body, hands, and feet. Second, the type of metaphor that dominates is anthropomorphic metaphor. "ngalem" tends to match parts of the human body with inanimate objects. Third, the animal metaphor type is used to describe a beautiful neck as if it were coiled like a snake, while the synthetic metaphor is used to "smile" at the beauty of the lips. Some informants still remember this expression but tend not to understand its meaning. Some informants also no longer introduce these expressions to their children or grandchildren. Implicitly, this research also illustrates the phenomenon of the Javanese community's declining interest in maintaining and passing on the language to the generations below.